Spectrum of Atazanavir‐Selected Protease Inhibitor‐Resistance Mutations - the EuResist Network Study Group (2022)
Funding Information: Conflicts of Interest: A.S. received research grants from Gilead Sciences, and personal fees for ad‐ visory boards from Gilead Sciences, MSD, and ViiV Healthcare, all outside the present work. M.Z. received research grants from Gilead Sciences, MSD, Theratechnologies and ViiV Healthcare and personal fees for advisory boards from Gilead Sciences, Janssen‐Cilag, MSD, Theratechnologies and ViiV Healthcare, all outside the present work. The funder had no role in the design of the study; in the collection, analyses, or interpretation of data; in the writing of the manuscript, or in the decision to publish the results. Funding Information: Funding: S.‐Y.R., A.J.B. and R.W.S. were supported in part by the National Institute of Allergy and Infectious Diseases (NIAID) of the National Institute of Health (NIH) (award number AI136618). The work of O.T. and D.K. was supported by the Russian Science Foundation Grant No. 19‐75‐10097. A.B.A. received funding from Fundação para a Ciência e Tecnologia through projects PTDC/SAU‐ INF/31990/2017 (INTEGRIV) and PTDC/SAU‐PUB/4018/2021 (MARVEL). G.D.T. was supported by EuResist Network GEIE. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.